Creativity of formal analysis in the study of ballroom dancing choreography - Issaliyev, Alibek; Moldakhmetova, Alima (Creativity Studies, 2025)
The article presents a structural analysis of the dynamics of position development in a pair in ballroom dancing with the use of research tools based on the method of formal analysis by Alexander Georgievich Gabrichevsky and the analysis of body movement in space by Rudolf von Laban. The aim of the study is to identify the distinctive features of the evolution of form in ballroom dancing. On the basis of formal analysis, the objectives of the research were to study ballroom dancing in spatial and temporal terms, to structure the dance form in vertical and horizontal planes, in the correlation of the categories of rhythm and meter, as well as in the context of static and dynamic time. The result of this study is a synthesis of the categories of space and time, which showed the leading trends in the development of the aesthetics of modern standard dances in the periods of modernism, postmodernism, and metamodernism. The comparative method made it possible to identify the characteristic features of the dynamics of form development in modern standard dances of the aforementioned periods. The uniqueness of the performing style in the categories of space, time, and their synthesis are revealed and analyzed. Illustrative examples of the study of the position of couples in the vertical and horizontal planes using the figure icosahedron are presented. The study also presents a conceptual map of the development of ballroom dancing in the context of the modern, postmodern, and metamodern eras. The main provisions of the study are the unity of spatial and temporal chronotope in ballroom dancing, considered as spatial and temporal parameters of expression of cultural and artistic meanings of modernity, postmodernity, and metamodernity, as well as the subordination of artistic time to rhythmic logic, based on metric alternations and movements, ordering the overall composition in the artistic space of ballroom dancing. This study provides a promising toolkit for analyzing the development and dynamics of forms in broad application in the fields of dancesport and choreographic art forms. It will also help to identify choreographic art in the cultural metamodern landscape.